The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s11886-003-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the surgical management of ischemic mitral regurgitation

Abstract: The surgical approach to ischemic mitral regurgitation (IMR) remains a topic of considerable controversy. Will coronary artery bypass alone suffice, or should the valve be intervened upon? The poor late survival of patients with IMR is well recognized, but it remains unknown if this can be altered by addressing the valve directly. And if surgery is undertaken, should the valve be repaired or replaced? The underlying mechanisms of IMR remain incompletely understood, and although current theory focuses on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Not surprisingly, certain clinical factors were associated with reduced survival; these included decreasing ejection fraction, increasing age, worse heart failure, and greater numbers of comorbid conditions. Others have identified similar risk factors for late mortality in patients having surgery for IMR [1,24]. Thus, in surgical patients, the preoperative status is critically important in determining long-term survival.…”
Section: Clinical Impact-survival and Other Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…Not surprisingly, certain clinical factors were associated with reduced survival; these included decreasing ejection fraction, increasing age, worse heart failure, and greater numbers of comorbid conditions. Others have identified similar risk factors for late mortality in patients having surgery for IMR [1,24]. Thus, in surgical patients, the preoperative status is critically important in determining long-term survival.…”
Section: Clinical Impact-survival and Other Outcomesmentioning
confidence: 94%
“…As noted previously, when such patients undergo CABG, a mitral valve procedure is generally indicated [4,5,24]. Currently, surgeons favor mitral valve repair for severe functional IMR.…”
Section: Revascularization With Mitral Valve Repairmentioning
confidence: 99%
“…Several different repair methods of the mitral valve have been investigated, some of which have been put into practical use, including the papillary muscle sling (22), papillary muscle relocation (13), and selective chordal cutting (7). The most commonly used surgical procedure to correct FIMR is coronary artery bypass grafting combined with ring annuloplasty, or either method alone (5,7,10). The results of recent studies (3,17) have shown that 30% of patients had a recurrence of significant ischemic mitral regurgitation during a six-month period after surgery, and that this was increased to 60% after three to five years (5).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, FIMR is seen in between 11% and 59% of patients after myocardial infarction (1). Even with a mild degree of mitral regurgitation, these patients have a mortality risk that is two-to fourfold higher than in those patients without mitral regurgitation within 2 to 16 days after infarction (10).…”
mentioning
confidence: 91%